Nanotechnology Approaches in Tackling Cardiovascular Diseases - Prajnamitra, Ray Putra (Molecules, 2019)
Cardiovascular diseases have continued to remain a leading cause of mortality and morbidity worldwide. Poor proliferation capability of adult cardiomyocytes disables the heart from regenerating new myocardium after a myocardial ischaemia event and therefore weakens the heart in the long term, which may result in heart failure and death. Delivery of cardioprotective therapeutics soon after the event can help to protect the heart from further cell death and improve cardiac function, but delivery methods and potential side effects of these therapeutics may be an issue. Advances in nanotechnology, particularly nanoparticles for drug delivery, have enabled researchers to obtain better drug targeting capability, thus increasing the therapeutic outcome. Detailed study of nanoparticles in vivo is useful as it can provide insight for future treatments. Nanogel can help to create a more favourable environment, not only for a sustained delivery of therapeutics, but also for a better navigation of the therapeutics to the targeted sites. Finally, if the damage to the myocardium is too severe for drug treatment, nanopatch can help to improve cardiac function and healing by becoming a platform for pluripotent stem cell-derived cardiomyocytes to grow for the purpose of cell-based regenerative therapy.